Government Support of Export Crediting: Implementation of the OECD Recommendations - M. V. Melnichuk (Управленческие науки)
Despite the ongoing sanction regimes, the Russian Federation is seeking to enhance the competitiveness of tradable goods and, hence, expand the international trade, increase exports and provide legal support for export crediting as a guarantee for maintaining the active trade balance of the country. until now the regulatory framework for export crediting in the Russian Federation is not complete: certain provisions of the Russian and international law related to the area under study need harmonization. In this paper, the author examines the compliance of the terms of the OECD Arrangement on Officially Supported Export Credits with the regulatory framework governing export crediting in the Russian federation. The paper analyzes the Russian legislation, strategic planning documents and in-house documents of organizations that form the national export support system. The analysis revealed the lack of legislative consolidation of export development in the Russian Federation, with regulatory issues reflected in non-core documents. The problem solution lies in improving the regulatory framework for support of export crediting so as to reduce the country risk and enhance the national competitiveness.